An in-vivo study on the release of nickel and chromium from fixed metallic orthodontic appliances - Ng Sinco, ChristineL; Yumiaco, Agnes S.; Lago, Leonor C. (Adviser).
This paper purposes to measure the amounts of nickel and chromium released from the fixed metallic orthodontic appliances in patients who have at least worn it for six months. The values obtained were compared to a control group (no orthodontic experience and no metallic restorations), and was found to be higher. However, the figures of 0.05 ug/ml for chromium and 0.06 ug/ml for nickel is far below the systemic toxic level of 3 mg. Nevertheless, the significance of this paper should not underestimated, since hypersensitivity to these metals does occur and should warn the dentist of its possibility in his next patient.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Orthodontic appliances; Orthodontic therapy